Aggression in a cohort of male methamphetamine (METH) users with and without Kkratom (Mitragyna speciosa Korth.): use history in Malaysia - Yang, Yuting; Müller, Christian P.; Singh, Darshan (Journal of psychoactive drugs, 2024)
Methamphetamine (METH) consumption is associated with aggression. Decoction derived from the kratom (Mitragyna speciosa Korth.) leaf has been used as a METH substitute in Southeast Asia. Given its perceived benefit, we investigated the relationship between kratom use and aggression in a treatment sample of METH users with and without kratom use history. Four hundred and three male METH users participated in this cross-sectional study. A semi-structured questionnaire and several objective clinical measures were administered. Results indicate that there were no significant differences in aggression and its dimensions between METH users with and without kratom use history. However, two distinct Clusters (1 and 2) of METH users with kratom use history were studied. Users in Cluster 1 were characterized by a higher quantity and frequency of daily kratom use, longer duration of kratom use, and use of kratom at a younger age. Users in Cluster 2 exhibited the opposite characteristics. Kratom dependence and the first age of kratom use were identified as risk factors for aggression in Cluster 1. The frequency of daily kratom use appeared as a protective factor against aggression in Cluster 2. The results offer partial support to the instrumental kratom use concept; lower frequency (1 to 3 times) of kratom use may potentially minimize aggression in METH users presenting with mild to moderate kratom dependence.